Carbon Dots Derived from Waste Psidium Guajava Leaves for Electrocatalytic Sensing of Chlorpyrifos. Issue 7 (10th January 2022) - Dash, Smruti Ranjan; Bag, Subhendu Sekhar; Golder, Animes Kumar
Abstract: Carbon dots (CDs) modified GCE was used for the electrochemical sensing of Chlorpyrifos (CHL). The hydrothermal synthesis (200 °C for 10 h) produced CDs of 3.7 nm using Psidium guajava leaves. Square wave voltammetry was employed for the determination of CHL and the electrokinetic parameters. The reduction of CHL involved an irreversible two‐electron process with heterogeneous reaction rate ( k° ) and formal potential (E°) of 1.21 s −1 and −1.34 V respectively. The modified GCEs exhibited good repeatability (RSD 4.7 %), reproducibility (RSD 1.17 %), and sensitivity (1.30 mA μM −1 cm −2 ). The detection limit and linear ranges were 1.5 nM and 0.01–1 μM, respectively. Electrochemical sensing of CHL was comparable with the HPLC (∼5 % variation). Abstract :